Table of Content - - (Arab Journal for Sciences and Research Publishing, 2025)
Table of Content: 1. The image of the General Entertainment Authority among a sample of male and female students at King Abdulaziz University Ms. Rahaf Hmeed Alotaibi ,Prof. Fatima kobibi Bendenia 2. Aesthetic Modernity and Its Dilemmas: Art between the Demand for Independence and the bet of Penetrating Public Space Mr. Ahmed Chebli 3. Social and Cultural Barriers to the Empowerment of Yemeni Women in Public Employment (An Analytical Field Study) Ms. Fatima Ali Abdullah Abbas 4. The pragmatic dimension of pronunciation in The Maqamat of Badi’ Al-Zaman Al-Hamdhani- the Maqamat Al-Harziyya as an example Ms. Alia Ali Saeed Alketbi, Dr. Muhammad Hilmi bin Abdullah bin Jaafar 5. The role of the media in spreading digital awareness among members of society in the Kingdom of Saudi Arabia Eng. Faris Omar Batawi, Ms. Doaa Hassan Toweirqie